The Effect of Banana Stem Fiber Mixtures on Mechanical and Physical Properties Using a Polyester and Vinylester Blend Matrix - M Rifki ALKindi; Rahmat Fajrul; Murdani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Natural fiber-reinforced composites continue to be developed as lightweight, economical, and environmentally friendly alternatives to metals and synthetic composites. One natural fiber with strong potential is banana stem fiber, which is easily obtained and helps reduce environmental waste. This study aims to determine the effect of adding banana stem fiber on the mechanical and physical properties of a composite using a mixed matrix of polyester resin (70%) and vinylester resin (30%). The composites were fabricated using the hand lay-up method with fiber mass variations of 0, 2, 5, 7, and 12 grams, and were subsequently tested for impact strength according to the ASTM D6110 standard. The results show that the addition of banana stem fiber significantly increased the impact strength of the composite. The specimen without fiber (0 grams) produced the lowest absorbed energy and impact strength values, while the 12-gram fiber variation showed the best performance, with an average absorbed energy of 11.66 Joules and the highest impact strength of 0.090 J/mm². Variations in values among specimens of the same composition are presumed to result from the hand lay-up fabrication process, such as uneven fiber distribution and the formation of voids. Overall, the composite with 12 grams of banana stem fiber in a 70% polyester–30% vinylester matrix was identified as the best composition in this study.